2013
DOI: 10.1002/hep.26302
|View full text |Cite
|
Sign up to set email alerts
|

A c-Myc-MicroRNA functional feedback loop affects hepatocarcinogenesis

Abstract: c-Myc (Myc) plays an important role in normal liver development and tumorigenesis. We show here that Myc is pathologically activated in and essential for promoting human hepatocellular carcinoma (HCC). Myc induces HCC through a novel, microRNA (miRNA)-mediated feedback loop comprised of miR-148a-5p, miR-363-3p, and ubiquitin-specific protease 28 (USP28). Myc directly binds to conserved regions in the promoters of the two miRNAs and represses their expression. miR-148a-5p directly targets and inhibits Myc, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 46 publications
2
96
0
Order By: Relevance
“…C-myc is also considered to be oncogene and frequently overexpressed in HCC [39][40][41]. Our present results revealed that Ang II enhanced C-myc immunofluorescent expression in HCC cell lines and the expression was predominantly cell nucleus.…”
Section: Discussionsupporting
confidence: 62%
“…C-myc is also considered to be oncogene and frequently overexpressed in HCC [39][40][41]. Our present results revealed that Ang II enhanced C-myc immunofluorescent expression in HCC cell lines and the expression was predominantly cell nucleus.…”
Section: Discussionsupporting
confidence: 62%
“…MYC directly regulates the expression of genes that encode the enzymes in the nucleotide biosynthetic pathways and in the feeder pathways for the production of the precursors of all nucleotides (15,2426), as well as coordinates RNA and protein biosynthesis (27,28). MYC also influences expression of specific microRNAs that regulate enzymes required for cell proliferation (22,2931). …”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of MYC promotes oncogenic transformation and tumorigenesis by activating the transcription of target genes that drive cell proliferation and stimulate angiogenesis and repress cell differentiation [13]. MYC is frequently overexpressed in HCC [14, 15, 16]. Tissue microarray analysis showed that up to 70% of human virus and alcohol-related HCC shows excessive activation of MYC [14].…”
Section: Introductionmentioning
confidence: 99%